DESAIN MODEL PURWARUPA AUGMENTED REALITY PATUNG KARWAR 4.0 SEBAGAI MEDIA PEMBELAJARAN SENI TRADISI BIAK PAPUA - wanda listiani; Sri Rustiyanti; Fani Dila Sari; IBG Surya Peradantha (Universitas PGRI Adi Buana Surabaya, 2020)
One of the cultural arts of the Papua Biak tribe that is still maintained in traditional ceremonies is the wor tradition and the making of karwar or korwar statues. Karwar statue as a shadow of the spirit and where Nin lives. The spirit of karwar or arawah gives the strength to look after the family, the garden, bring rain, keep away diseases and so on. The re-introduction of the karwar statue using AR technology is one way for young people to be interested in the existence of Biak tribal arts and culture. This study used a static visualization method that shows phenomena or processes in the form of a representation of the design path of the AR PASUA PA prototype model specifically the spatial and temporary entities of the AR Karwar Biak Papua Statue. The results of this study illustrate the modeling concept and procedure model developed in the design of the AR Karwar 4.0 prototype model by considering the needs of users and the problems of artists, connoisseurs and pedagogic of cultural arts learners, especially the cultural arts of Biak Papua